The Effect of Extra Virgin Olive Oil to Decrease HSP-90, TNF-Α and ET-1, in Pre-Eclampsia Rat Model - Wenny Rahmawati (Journal of Global Pharma Technology, 2020)
ABSTRACTBackground: Preeclampsia characterised by new-onset hypertension with systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg, measured on two occasions at least four hours apart, and proteinuria of > 0.3 g per 24 hours or ≥ 1+ proteinuria, detected by urine dipstick after 20 weeks of pregnancy, or in the absence of proteinuria. Objectived: This study aimed to determine effect of EVOO as a strong exogenous antioxidant to decrease TNF-α, HSP-90 and ET-1 level in preeclampsia rat model. Method: This research consisted of five groups; negative control, positive control (preeclampsia rat model), doses 1, 2, and 3 that were preeclampsia rats given EVOO in 3 different doses (0.5 mL/day, 1 mL/day and 2 mL/day respectively). After sacrificed, placentas were collected to determine HSP-90, TNF-α and  ET-1 level. Result: Result of this study showed that there was a reduction of HSP90 (p=0,00), TNF-α (p=0.011), ET-1 (p=0.02). Conclusion: Administration EVOO decreased HSP-90, TNF-α and ET-1 Level in preeclampsia rat modelKeywords: Preeclampsia, EVOO, HSP-90, TNF-α, ET-1,  Antioxidant, Oxidative stress.